Comparison of targeted proteomics approaches for detecting and quantifying proteins derived from human cancer tissues. Issue 5 (22nd February 2017) - Faktor, Jakub; Sucha, Rita; Paralova, Vendula; Liu, Yansheng; Bouchal, Pavel
Abstract : Targeted mass spectrometry‐based proteomics approaches enable the simultaneous and reproducible quantification of multiple protein analytes across numerous conditions in biology and clinical studies. These approaches involve e.g. selected reaction monitoring (SRM) typically conducted on a triple quadrupole mass spectrometer, its high‐resolution variant named pseudo‐SRM (p‐SRM), carried out in a quadrupole coupled with an TOF analyzer (qTOF), and "sequential window acquisition of all theoretical spectra" (SWATH). Here we compared these methods in terms of signal‐to‐noise ratio (S/N), coefficient of variance (CV), fold change (FC), limit of detection and quantitation (LOD, LOQ). We have shown the highest S/N for p‐SRM mode, followed by SRM and SWATH, demonstrating a trade‐off between sensitivity and level of multiplexing for SRM, p‐SRM, and SWATH. SRM was more sensitive than p‐SRM based on determining their LOD and LOQ. Although SWATH has the worst S/N, it enables peptide multiplexing with post‐acquisition definition of the targets, leading to better proteome coverage. FC between breast tumors of different clinical‐pathological characteristics were highly correlated ( R 2 >0.97) across three methods and consistent with the previous study on 96 tumor tissues. Our technical note presented here, therefore, confirmed that outputs of all the three methods were biologically relevant and highly applicable to cancer research.